Comparing the Cardiovascular Risk of Norethindrone Acetate & Levonorgestrel Pills: Is There a Difference? [10I]. (May 2020) - Barnett, Clare; Bauerfeind, Anja; von Stockum, Sophia; Grimes, David A.; Heinemann, Klaas
Abstract : INTRODUCTION: Combined oral contraceptives containing norethindrone acetate (NETA) are widely used in the US and globally, but how they compare to levonorgestrel-containing pills is unknown. This pooled analysis compares the safety of NETA and levonorgestrel (LNG) in pills with ethinyl estradiol (EE) ⩽30 mcg. METHODS: We pooled cohorts of NETA (EE ⩽30 mcg) and LNG (EE ⩽30 mcg) users from four large prospective, controlled, non-interventional, cohort studies in 14 European countries, US and Canada. Baseline characteristics, including reproductive, contraceptive and medical history, were summarized using descriptive statistics. Propensity score sub-classification was applied to balance baseline characteristics between cohorts. Time-to-event analysis of venous and arterial thromboembolic events was carried out based on the extended Cox model to calculate crude and adjusted hazard ratios with 95% confidence intervals. RESULTS: Approximately 80, 000 women contributed 145, 000 women years of exposure. The prevalence of prognostic factors at baseline showed typical features of US and European oral contraceptive users. A comparison between NETA vs LNG showed no significant difference in the risk of venous thromboembolism: adjusted hazard ratio 0.73 (95% CI 0.48-1.11). A similar result was observed considering the risk of arterial thromboembolism (adjusted hazard ratio 0.89 [95% CI 0.42-1.89]). CONCLUSION: Low-dose oral contraceptives containing NETA and LNG are associated with similar low risks of venous and arterial disease. This analysis provides reassurance for both women and clinicians regarding the safety of contemporary oral contraceptives.